Uncertainty and bargaining: A structural econometric approach - Gordon Klein; Mayra Rebolledo (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2020)
This paper proposes a structural econometric model to analyze the influence of uncertain disagreement outcomes on the settlement of new agreements between parties with uneven bargaining power. By including the the findings of theoretical literature on the requirements to reach agreements under uncertain disagreement conditions, and using an asymmetric Nash bargaining framework, our proposal is able to estimate not only the bargaining solutions but also the bargainers' uncertainties and determine whether a new compromise could be reach under such uncertainty or not.
Keywords: 330